PELATIHAN DESAIN GRAFIS UNTUK MENINGKATKAN KREATIVITAS PADA SISWA SMK TARBIYATUL AULAD MENGGUNAKAN SOFTWARE COREL DRAW - Yanti, Yanti; Sumiarsih, Mia; Sutisna, Agus; Rusdja, Andy Permana; S, Yadi (Sekolah Tinggi Ilmu Ekonomi AMA, 2024)
At this time the computer has many applications that can help work and can increase creativity. Corel Draw is one of the graphic design software used in designing logos, posters, banners, invitations, and advertisements. This training aims to provide insight and knowledge, as well as new skills to students so that students can improve their abilities in the computer field, especially in graphic design and students are able to express their creative ideas in the form of graphic design in the form of posters. Graphic design training was held at SMK Tarbiyatul Aulad. SMK Tarbiyatul Aulad is a Vocational High School with accreditation A, registered with SK number: 08/YAY-TA/I/2012, NPSN number 69758144, located at Kp. Ngamplang Cibodas Village Cikajang District Garut Regency, West Java Province. SMK Tarbiyatul Aulad is under the auspices of Tarbiyatul Aulad Cikajang Foundation. The training activities were attended by 22 students of SMK Tarbiyatul Aulad. The graphic design training provided was in the form of poster making training. After the training, the students can make posters using Corel Draw software.